How should the severity of depression be rated on self-report depression scales?. (October 2019) - Zimmerman, Mark; Kerr, Sophie
Highlights: The most valid rating format of depression severity scales is unsettled and has been little studied. We compared the validity of alternative approaches towards rating the severity of depressive symptoms. Symptom ratings based on intensity and frequency were highly correlated with each other. Symptom ratings based on intensity and frequency were equally highly correlated with external validators. Ratings of depressive symptoms based on either symptom intensity or symptom frequency are equally valid. Abstract: Almost all depression measures have been developed without discussing how to best conceptualize and assess the severity of depression. The most valid rating format of depression severity scales is unsettled and has been little studied. In the present study from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project, we compared the validity of alternative approaches towards rating the severity of depressive symptoms. Data was collected using TurkPrime. One hundred eighty-five participants currently in treatment for a mental health problem completed a self-report measure of depression and rated the symptoms on two 4-point ordinal scales assessing symptom frequency and symptom intensity. The respondents also rated their global level of depression severity and completed a measure of psychosocial functioning and quality of life. The symptom ratings based on intensity and frequency were highly correlated with each other, and equally highly correlated with subjects' global rating of overall severity of depression, as well as ratings of psychosocial functioning and quality of life. A composite index of severity based on the sum of frequency and severity ratings was no more highly correlated with the external validators. The results of the present study suggest that ratings of depressive symptoms based on either symptom intensity or symptom frequency are equally valid.